OCHRONA MAJĄTKU POSAGOWEGO W KONTEKŚCIE MANUMISSIO SERVI DOTALIS - Stępkowska, Agnieszka (Zeszyty Prawnicze, 2017)
Manumissio servi dotalis and the Protection of Dowry in Roman Law Summary As opposed to a widespread opinion, examination of legal sources shows, the Roman law neither prohibited manumissio servi dotalis, nor it required wife’s consent. It does not mean, dowry could be freely reduced by means of manumissio. Value of the dowry was still protected by the rules of subrogation, applicable to all the assets acquired by husband iure patroni. However, subrogation did not apply to assets received by husband from his libertinus and exceeding what was required by the rules of patronage. Manumissio, to which wife opposed was perfectly valid in law, however it was not praised. In such a case, income from the patronage was acquired directly by wife and only the surplus was subject to subrogation as a dowry. Sources consider as a manumissio servi dotalis also those situations, in which, the manumitted slave was, strictly speaking, no longer part of the dowry. In such a cases where was no subrogation of course. There were two types of such a situation. The first concerned dotis aestimatio, with which dowry ceased to form a distinct patrimony and became only a husband’s debt, due to wife with the end of marriage. In such a case there was no place for subrogation. Wife’s dowry interest was protected only by the prohibition of manumissiones in case of husband’s insolvency. This however was ordinary means of protecting all creditor against fraus creditorum not a specific solution for servus dotalis. The second type of such a situation rose when wife consented to exclude a slave out of the dowry. Similarly, the slave was no longer part of dowry and all the advantages received from him by husband as a patron were his personal. In this case dowry was indeed diminished, nevertheless wife approved it.